Urban household food security in China and Mozambique: a gender-based comparative approach. Issue 8 (17th November 2018) - Riley, Liam; Caesar, Mary
ABSTRACT: International comparison of development indicators is a perennial challenge in global development studies. The challenge is especially difficult when measuring urban household food security using experience-based metrics that are influenced by countless contextual factors. This article presents a gender-based analysis of household food security surveys conducted in Nanjing, China and Maputo, Mozambique. The analysis demonstrates the value of a gender lens for understanding the intersecting household characteristics associated with urban food insecurity. While Maputo had much higher food insecurity overall, our analysis leads to nuanced insights into shared and divergent connections between gender inequality and food insecurity in both cities.